EVALUASI KEAMANAN SUMBER AIR MINUM DESA MOJO KECAMATAN PADANG KABUPATEN LUMAJANG - Aditya Oktavianto; Nurhayati Nurhayati; Enny Suswati (JURNAL AGROTEKNOLOGI, 2014)
Little known about the safety of natural water on enteric mikroflora population at Mojo Village Padang Distric Lumajang Regency. We assessed the population of enteric microflora i.e Salmonella and Eschericia coli in the wellspring. We performed a randomized sampling to evaluate the population of Salmonella and Eschericia coli of three natural water resource at Mojo Village. There were Jirun, Kali Tengah and Sumber Suko water resource. Medium to colony identification were used Salmonella Chromogenic Agar (SCA) and Enteric Hektoin Agar (HEA). SCA resulted blue colony for Eschericia coli and magentha or violet colony for Salmonella. While HEA resulted orange colony for Eschericia coli and green for Salmonella. 250 mL of natural water was used to growth the enteric microflora. We observed three water resource of Mojo Village contain enteric microflora. The enteric microflora population was up to 2 log10 CFU/mL (more than 10 CFU/mL). These was a fantastic population, because enteric population must no growth on drink water. Assuming the enteric microflora come from fish faecal, because at the surrounding of water resource growth the fish. Three water resource at Mojo Village were no safety to used as drink water if without water treatment. The enteric microflora can dextructed by using filtration and UV treatment or thermal process example water boiling.Keywords: Jirun, Kali Tengah, Sumber Suko, Salmonella, Eschericia coli, water resource